An SECE array of piezoelectric energy harvesting. (25th February 2021) - Wu, P H; Lin, J T; Lo, Y C; Shu, Y C
Abstract: The paper studies the electrical response of an array of piezoelectric oscillators attached to the synchronized electric charge extraction (SECE) interface circuit. The analytic estimate of output power is derived and presented through the matrix formulation of generalized Ohm's law (charging on capacitance) for the case of parallel (series) connection of energy harvesters. These formulations mainly depend on the proposed equivalent load impedances which are independent of external resistive loads. It therefore offers an advantage of enabling harvested power independent of DC output voltage and making the harvester array desirable for broadband energy scavenging. The proposed framework is subsequently validated both numerically and experimentally. The results show that the power output and bandwidth of an SECE-based array are superior to that based on the standard energy harvesting circuit. Further, it is found that the behavior of an SECE array electrically arranged in parallel connection is different from that connected in series. The former demonstrates the output power higher than the latter, while the latter exhibits roughly uniform peak power in frequency response. However, the experiment indicates the unexpected power drop deviated significantly from the prediction in the array of harvesters connected in series. Such a discrepancy is explained as a result of comparatively serious leakage current in the reverse-biased diodes.